Data envelopment analysis for ambulance services of different service providers in urban and rural areas in Ministry of Health Malaysia - Mohd Hassan, Nor Zam Azihan; Bahari, Mohd Shahri; Aminuddin, Farhana; Mohd Nor Sham Kunusagaran, Mohd Shaiful Jefri; Zaimi, Nur Amalina; Mohd Hanafiah, Ainul Nadziha; Kamarudin, Fakarudin (Frontiers Media SA, 2023)
Introduction: Ambulance services are pivotal in any country's healthcare system. An efficient ambulance service not only decreases patient mortality rate but also allows resource prioritization for better outputs. This study aims to measure the efficiency of ambulance services provided by health facilities in the Ministry of Health (MOH), Malaysia.